Melupakan Great Chain of Being Intelektual Muslim Dalam Tegangan Antara Sekularisme dan Skizofrenia Kultural - Alfathri Adlin; Yasraf Amir Piliang; Bambang Sugiharto; Irma Damajanti (Jurnal Peradaban, 2023)
The integration of (post)modern Western thought by some Indonesian Muslim intellectuals needs to be critiqued regarding, first, the modern historical bias as progress, which leads to the appropriation of the latest thoughts into Islamic thinking as a sign of progress and openness. Second, the forgetting of the Great Chain of Being, resulting in the adaptation and revision of Islamic thought through the dynamics of Western (post)modern thought born from different historical contexts. Third, the tendency to graft secularism as a historical inevitability in the Islamic world, as well as the cultural schizophrenia among educated Muslims when integrating secular (post)modern knowledge into Islamic teachings and its hierarchical structure of reality.